2008
DOI: 10.1111/j.1469-7998.2008.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional regionalization of the pectoral fin of the benthic longhorn sculpin during station holding and swimming

Abstract: Studies of the kinematics of the pectoral fins in fishes have focused on fins as devices for propulsion or maneuvering. Studying pectoral fin function in benthic fishes is an opportunity to understand how the fins are used in a broader range of fin-based behaviors, especially those involving substrate contact. Morphological specializations of the pectoral fins, hypothesized adaptations for substrate contact, have been described for several benthic fish groups. These specializations include, but are not limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 22 publications
4
55
0
Order By: Relevance
“…Currently, we know of only two studies that have measured the curvature of individual fin rays during locomotion [dorsal and anal fins of bluegill sunfish (Standen and Lauder, 2005), pectoral fins of longhorn sculpin (Taft et al, 2008)]. However, in both of these studies, curvature was measured only along the length of the fin rays, irrespective of the fin surface.…”
Section: Introductionmentioning
confidence: 97%
“…Currently, we know of only two studies that have measured the curvature of individual fin rays during locomotion [dorsal and anal fins of bluegill sunfish (Standen and Lauder, 2005), pectoral fins of longhorn sculpin (Taft et al, 2008)]. However, in both of these studies, curvature was measured only along the length of the fin rays, irrespective of the fin surface.…”
Section: Introductionmentioning
confidence: 97%
“…Curvature () is defined as the change in the unit tangent vector divided by the change in the arc length curve (Taft et al, 2008). One caveat regarding the use of splines to estimate curvature is that they can yield spurious local peaks in curvature at the knots where one piecewise polynomial function is replaced by the next.…”
Section: Estimation Of Fin Ray Curvaturementioning
confidence: 99%
“…They use their large, fan-like pectoral fins to support their weight and rapidly push off from the substrate as well as for swimming in the open water (Taft et al, 2008). It has been shown that the pectoral fin of this species is functionally regionalized, with the more ventral rays being used for direct substrate contact and the dorsal rays being used during slow swimming (Taft et al, 2008). The individual lepidotrichia are also divided into distinct morphological regions (Fig.1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations